Behavioural responses to heat in an arid-zone bird vary with thermal, hygric and social factors - J. R. D. Whyte; A. E. McKechnie; J. K. Crossley; S. J. Cunningham (Oecologia, 2026)
The severity of fitness costs resulting from behavioural trade-offs between heat dissipation and activities such as foraging is increasing with advancing climate change. In terrestrial habitats, shade and water may buffer individuals from the negative effects of heat exposure, as may load-lightening in group-living species. We tested the hypothesis that thermal and hygric properties of home ranges (shade and water availability) and social factors (group size) influence the costs associated with hot weather, using a population of white-browed sparrow-weavers ( Plocepasser mahali ) in the southern Kalahari Desert. Across all sparrow-weaver groups, heat avoidance (shade-seeking) and dissipation (panting) behaviours increased with increasing air temperature ( T air ), whereas foraging declined. Birds occupying shadier home ranges delayed the onset of panting to higher T air and foraged less while maintaining overall peck rates. Birds with access to water foraged more, maintained higher peck rates and sought shade at higher T air compared to birds without. However, they did not pant more, making the mechanism underpinning their increased foraging effort unclear. Birds in larger groups both panted more overall and sought shade at lower T air than birds in smaller groups but maintained similar overall peck rates. Taken together, these results suggest birds in shadier home ranges can forage more efficiently, buffering foraging costs at high T air . Our data therefore suggest that some impacts of increasing T air under climate change can be buffered by shade availability, but the impacts of water availability and social factors are less clear.

The COSPAR planetary protection policy for missions to Icy Worlds: A review of history, current scientific knowledge, and future directions - P.T. Doran; A. Hayes; O. Grasset; A. Coustenis; O. Prieto-Ballesteros; N. Hedman; O. Al Shehhi; E. Ammannito; M. Fujimoto; F. Groen; J.E. Moores; C. Mustin; et al. (Life Sciences in Space Research, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic diversity of provitamin-A cassava (Manihot esculenta Crantz) in Sierra Leone - I. Kamanda; E. T. Blay; I. K. Asante; A. Danquah; B. E. Ifie; E. Parkes; P. Kulakow; I. Rabbi; A. Conteh; J. S. Kamara; H. K. Mensah; J. B. A. Whyte; et al. (Genetic Resources and Crop Evolution, 2020)
Understanding the genetic diversity among accessions and germplasm is an important requirement for crop development as it allows for the selection of diverse parental combinations for enhancing genetic gain in varietal selection, advancement and release. The study aimed to characterize 183 provitamin A cassava ( Manihot esculenta Crantz) accessions and five Sierra Leonean varieties using morphological traits, total carotenoid content and SNP markers to develop a collection for conservation and further use in the cassava breeding program. Both morphological parameters and 5634 SNP markers were used to assess the diversity among the provitamin-A cassava accessions and varieties. Significant differences were observed among the accessions for most of the traits measured. The first five PCs together accounted for 70.44% of the total phenotypic variation based on yield and yield components among the 183 provitamin-A cassava accessions and five Sierra Leonean varieties. The present study showed that provitamin-A cassava accessions in Sierra Leone have moderate to high diversity based on morphological and molecular assessment studies. The similarity index among the 187 and 185 cassava accessions grouped them into 6 and 9 distinct clusters based on morphological and molecular analyses, respectively. A significant positive, but low correlation ( r = 0.104; p < 0.034), was observed between the two dendrograms. The results obtained will serve as a guide and basis of germplasm management and improvement for total carotenoid content, yield and African cassava mosaic disease resistance in Sierra Leone.

A fixed‐dose approach to conducting emamectin benzoate tolerance assessments on field‐collected sea lice, Lepeophtheirus salmonis - S K Whyte; J D Westcott; A Elmoslemany; K L Hammell; C W Revie (Journal of Fish Diseases, 2013)
In N ew B runswick, C anada, the sea louse, L epeophtheirus salmonis, poses an on‐going management challenge to the health and productivity of commercially cultured A tlantic salmon, S almo salar . While the in‐feed medication, emamectin benzoate ( SLICE ® ; M erck), has been highly effective for many years, evidence of increased tolerance has been observed in the field since late 2008. Although bioassays on motile stages are a common tool to monitor sea lice sensitivity to emamectin benzoate in field‐collected sea lice, they require the collection of large numbers of sea lice due to inherent natural variability in the gender and stage response to chemotherapeutants. In addition, sensitive instruments such as EC 50 analysis may be unnecessarily complex to characterize susceptibility subsequent to a significant observed decline in efficacy. This study proposes an adaptation of the traditional, dose–response format bioassay to a fixed‐dose method. Analysis of 657 bioassays on preadult and adult stages of sea lice over the period 2008–2011 indicated a population of sea lice in N ew B runswick with varying degrees of susceptibility to emamectin benzoate. A seasonal and spatial effect was observed in the robustness of genders and stages of sea lice, which suggest that mixing different genders and stages of lice within a single bioassay may result in pertinent information being overlooked. Poor survival of adult female lice in bioassays, particularly during M ay/ J une, indicates it may be prudent to consider excluding this stage from bioassays conducted at certain times of the year. This work demonstrates that fixed‐dose bioassays can be a valuable technique in detecting reduced sensitivity in sea lice populations with varying degrees of susceptibility to emamectin benzoate treatments.

Sea lice monitoring on A tlantic salmon farms in N ew B runswick, C anada: comparing audit and farm staff counts - A Elmoslemany; S K Whyte; C W Revie; K L Hammell (Journal of Fish Diseases, 2013)
Sea lice audits were performed by the A tlantic V eterinary C ollege on commercial aquaculture sites in N ew B runswick, C anada, in 2011. Although the primary objective was to verify that farms were reporting similar lice counts to third‐party counts, more detailed comparisons were made to identify when lice counts were more likely to differ between the audit team and farm employees. A total of 28 sea lice audits were conducted on 16 sites between J une and D ecember 2011. During each audit, 10 cages were evaluated per site where possible, with ten fish per cage being evaluated by an audit technician and a further ten by a farm employee. Data analysis included descriptive statistics of lice counts by stage and limits of agreement plots. A random effects negative binomial model that accounted for clustering of cages within sites was applied to assess the effect of counter type and season on lice counts by stage. The results indicate that farms counts were generally in agreement with audit counts. However, when the average counts for chalimus and preadult (male and female) and adult male lice stages were high, farm counters were more likely to report a lower value. Higher lice counts were observed during autumn compared to summer especially for the adult female stage. Finally, there was a significant clustering effect for site and cage, with most of the variation attributable to site.

Vascular endothelium-specific overexpression of human catalase in cloned pigs - J. J. Whyte; M. Samuel; E. Mahan; J. Padilla; G. H. Simmons; A. A. Arce-Esquivel; S. B. Bender; K. M. Whitworth; Y. H. Hao; C. N. Murphy; E. M. Walters; R. S. Prather; et al. (Transgenic Research, 2011)

Reply to: do marathon runners face an “ominous” risk of myocardial fibrosis? - M. G. Wilson; R. O’Hanlon; S. K. Prasad; S. Sharma; K. George; G. Whyte (European Journal of Applied Physiology, 2011)

Cardiovascular function and the veteran athlete - M. Wilson; R. O’Hanlon; S. Basavarajaiah; K. George; D. Green; P. Ainslie; S. Sharma; S. Prasad; C. Murrell; D. Thijssen; A. Nevill; G. Whyte (European Journal of Applied Physiology, 2010)

The upper limit of physiological cardiac hypertrophy in elite male and female athletes: the British experience - G.P. Whyte; K. George; S. Sharma; S. Firoozi; N. Stephens; R. Senior; W.J. McKenna (European Journal of Applied Physiology, 2004)